Voldbækgravpladsen – Yngre jernalder, vikingetid og middelalder ved Brabrand Sø - Jeppesen, Jens (Kuml, 2010)
The Voldbæk cemetery The Late Iron Age, Viking and High Medieval periods by Brabrand Sø The Viking period cemetery at Voldbæk in Brabrand, about 6 km west of Århus, was investigated by Aarhus Museum in the period 1926-36, and the results of these investigations were published in 1936 in Johannes Brøndsted’s overview of Viking Age inhumation graves in Denmark. This site will be subjected here to a re-analysis on the basis of archival material from Aarhus Museum. The cemetery was discovered in 1926, during gravel extraction a short distance to the west of Brabrand. Up until 1931, 23 graves were examined as they appeared (fig. 1). It is these graves which were published by J. Brøndsted in 1936. The cemetery lay on a slope running down to the north shore of Brabrand Sø (Lake) (fig. 2). Across the cemetery as a whole, it is stated that the predominant orientation of the graves was east-west, and that the deceased were most commonly placed with their head to the west. The skeletons, of which some were well-preserved, lay most often in a supine position. Some were, however, laid in hocker position. No traces of coffins were found. Some graves were covered with large stones. Many of them were found to contain a single, worn iron knife and a whetstone, most commonly placed at the hip. Occasional graves contained richer and more diverse equipment. In addition to this general account, there is also a meticulous description of the graves, supplemented by numerous photographs and drawings that have not previously been made public. Collectively, this information forms the basis for the following account of the cemetery where reference is made to the revised site plan (fig. 3). In total, 26 graves were examined at the Voldbæk cemetery (figs. 12-43), but the actual number of graves was greater. In connection with graves 3 and 26, mention is made of remains of child graves, and close to grave 24 there was a further grave which was apparently not investigated. This brings the total up to 29 graves. Further to these, skeletons had been found prior to the museum being contacted. The cemetery was therefore at least 1/3 greater than the 23 graves presented by Brøndsted. The skeletal material from the Voldbæk cemetery was not retained, but on the basis of descriptions of the individual graves, together with the photos, a certain amount of information can be obtained concerning those interred. In connection with the accounts of the individual skeletons there is, repeatedly, an evaluation of sex and age (young or old) as well as a statement of height. The basis for this information is unknown – only in two cases (graves 20 and 26) is it mentioned that a doctor was present at their excavation. In five cases (graves 2, 8, 9, 13 and 24), the deceased is identified as being a man, whereas three graves (graves 3, 7 and 20) are said to be those of women. For three of the skeletons said to be men, their height is given, respectively, as 1.72 m (grave 2), 1.80 m (grave 8) and 1.73 m (grave 24). For one of the skeletons said to be a woman, her height is given as 1.55 m (grave 20). Grave 19 (height 1.40 m) should probably be assigned to the women’s graves as research in recent times has revealed that Thor’s hammers occur primarily in female graves. Even though the information should be taken with some reservation, it is apparent that the skeletons considered to be those of men are taller than those considered to be of women. This is consistent with the most recent investigations of Danish finds of skeletons from the Viking Age where the average height for men is given as 1.71 m, while that for women is 1.58 m. The information given on the dental state of the deceased is significant as it can be considered to be based on very reliable observations, in some cases confirmed by photographs. In six of the skeletons (graves 2, 3, 9, 20, 22 and 23), extensive tooth loss has been recorded as well as overgrown tooth alveoli. Conversely, in six other instances (graves 8, 13, 18, 19, 21 and 25) mention is made of a complete set of teeth which is, in several cases, described as “beautiful”. In a single case (grave 21), heavy tooth wear is mentioned. A nationwide investigation of skeletal material from the Viking period has shown that poor dental health with more or less expressed tooth loss was common. The toothlessness seen in some of the skeletons from the Voldbæk cemetery is therefore not remarkable. With regard to the dating of the Voldbæk cemetery, Brøndsted mentions a disc brooch in grave 3 as the only date-conferring find. This ornament in Jelling style is assigned by him to the end of the 10th century. More recent research, however, dates the Jelling style to most of the 10th century, with its beginning just prior to AD 900. This type of disc brooch also occurs in a coin-dated grave from Birka, with the latest coin being from AD 951-54. This date also corresponds to that of the Voldbæk cemetery’s grave 19, containing the Thor’s hammer. This amulet type is found primarily in graves from the 10th century. In addition to the above-mentioned examples from Birka and Brabrand, disc brooches of this kind have also been found at Haithabu and the Viking period cemetery at Stengade II on Langeland. Brøndsted believes that graves 21-23, with the deceased laid in hocker position, might be older than the Viking period. Two stray finds from the area are perhaps able to support this presumption. These comprise two fibulas from the 7th century (fig. 4). They were found immediately east of the Viking period cemetery, and they could belong to an earlier phase of the cemetery. The Voldbæk cemetery was probably sited in the vicinity of a settlement. If it does contain graves from both the Late Iron Age and the Viking period, as presumed, then there are a couple of settlement sites near Brabrand which could be of relevance (fig. 5). In 2005, two settlement pits from the Late Iron Age were discovered immediately NE of Brabrand Sø. One of them contained pottery (fig. 6) and a complete rotary quern (fig. 7). The other pit lay a few metres away and is interpreted as a well. The two pits undoubtedly reflect the presence of a settlement at this location and this settlement can, on the basis of the pottery, be assigned to the late 6th century. The distance from the Voldbæk cemetery is c. 3 km. This considerable distance, and the dating of the settlement, makes it seem unlikely that there was a direct link between cemetery and settlement. The settlement finds do demonstrate, however, that in the area immediately north of Brabrand Sø there was habitation during the Late Iron Age, and a later phase of this settlement perhaps lies closer to the cemetery. With respect to settlement traces that can be linked to the Viking period graves, the situation is very interesting. In connection with construction work in Brabrand in 1981, a large pit was partially uncovered. In this were found potsherds (fig. 8), a horse tooth and two small fragments of rib bones – probably of pig or sheep. The pottery dates the find to the Viking period. It could represent a refuse pit or a pit-house. Regardless of how the pit should be interpreted it reflects the presence of a Viking period settlement c. 500 m east of the Voldbæk cemetery (fig. 2). A distance of this order between the settlement and cemetery appears very likely if a comparison is made with the results of Moesgård Museum’s investigations at Randlev, SE of Odder. Here, a Viking period settlement and its cemetery were excavated in full and the settlement lies a few hundred metres from the cemetery. The settlement comprises a single farmstead dated to the 9th-10th century, and the associated cemetery contains rather more than 100 graves. Seen against this background, the Voldbæk cemetery, with its c. 30 burials, must undoubtedly also represent a single farmstead and it must have existed at least until the Late Viking period, 10th century. The sparsely equipped graves say nothing of the status of this farmstead. The cemetery at Randlev was generally very sparsely equipped, and here the settlement itself demonstrated a surprising richness in metal. The finds described above show that, perhaps in the Late Iron Age, and certainly in the Late Viking period, there was a settlement in the area lying immediately to the west of the village of Brabrand. The site’s possible relationship to the continuing settlement history in the area is interesting. Here, attention falls quite naturally on “Hovgaard” which lies detached directly on the north shore of Brabrand Sø, 300 m SW of the village and c. 450 m east of the Voldbæk cemetery (fig. 9). Historians have demonstrated that Hovgaard represents the remains of a village manor or home farm which belonged to a noble family in the Middle Ages. Excavations at Hovgaard in 1966 revealed foundations of granite boulders which, on the basis of pottery finds, can be dated to the 13th-14th century (fig. 10). The extent to which the site’s history extends further back in time cannot be determined on the basis of the excavation results. However, if this is the case, it is conceivable that this isolated farmstead on the north shore of Brabrand Sø is the successor to a farmstead which lay in this area, with its cemetery, in the Late Viking period. If Hovgaard’s special status has its origin in Viking times then it seems obvious to make comparisons with the situation at Lisbjerg, 7 km to the north of Århus. Excavations here have demonstrated that it was the site of the first church construction associated with a large isolated farmstead from the Late the Viking period. If the same were the case in Brabrand, this could explain the remarkably low-lying position of Brabrand Church relative to its village, being sited almost down on the shore of Brabrand Sø (figs. 2 and 11). The new analysis of the Voldbæk cemetery presented here shows that significant information can be added to this site. By involving evidence from settlement traces found around Brabrand, an attempt has been made to put the cemetery into a broader perspective. As a result, it seems likely that the medieval power centre, which historians have demonstrated in the area, could have its origins in the Viking Age. As a consequence, finds from the district become of interest relative to Viking Age Århus as the relationship between the town and its hinterland could have influenced development in both places. Jens Jeppesen Moesgård Museum